2021
DOI: 10.1093/jmammal/gyab108
|View full text |Cite
|
Sign up to set email alerts
|

Climatic dissimilarity associated with phylogenetic breaks

Abstract: Shared phylogenetic breaks often are associated with clear geographic barriers but some common phylogeographic breaks may lack obvious underlying mechanisms. A phylogenetic break involving multiple taxa was found in the Baja California Peninsula that was associated with a past sea barrier. However, geological evidence is lacking for this barrier’s past existence, and despite its current absence, the genetic breaks have persisted. This work explores the relationships between the current climatic niches for matr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 89 publications
0
2
0
Order By: Relevance
“…It may be that peninsulas and linear coastlines are particularly conducive for this phenomenon. Second, divergence is amplified under differential selection for low‐dispersing species; along the arid Baja peninsula, there is a strong gradient in the annual amount and seasonality of precipitation (Avila‐Lovera & Garcillán, 2021; Cab‐Sulub & Álvarez‐Castañeda, 2021), both controlled by the North American monsoon (Adams & Comrie, 1997; Higgins et al, 1999), which suggests differential adaptation may also be an important factor for interpreting this signal (Klimova et al, 2018). Importantly, species do not have the same physiology and niche constraints and therefore are not expected to be equally impacted by this gradient.…”
Section: Discussionmentioning
confidence: 99%
“…It may be that peninsulas and linear coastlines are particularly conducive for this phenomenon. Second, divergence is amplified under differential selection for low‐dispersing species; along the arid Baja peninsula, there is a strong gradient in the annual amount and seasonality of precipitation (Avila‐Lovera & Garcillán, 2021; Cab‐Sulub & Álvarez‐Castañeda, 2021), both controlled by the North American monsoon (Adams & Comrie, 1997; Higgins et al, 1999), which suggests differential adaptation may also be an important factor for interpreting this signal (Klimova et al, 2018). Importantly, species do not have the same physiology and niche constraints and therefore are not expected to be equally impacted by this gradient.…”
Section: Discussionmentioning
confidence: 99%
“…These breaks may arise when allopatric populations have experienced long-term isolation across major physiographic barriers to dispersals, such as mountains, rivers, glaciers, and oceans ( Soltis et al, 2006 ; Jaramillo-Correa et al, 2009 ). However, sometimes obvious physical barriers are absent and climate or habitat barriers play a more important role ( Geffen et al, 2004 ; Bai et al, 2016 ; Cab-Sulub and Álvarez-Castañeda, 2021 ). In a given area, co-distributed species may exhibit common phylogeographic breaks because they have a shared biogeographic history ( Arbogast and Kenagy, 2001 ; Soltis et al, 2006 ), but diverse patterns are more frequently observed reflecting the complex history affected by not only a few barriers ( Soltis et al, 2006 ; Shafer et al, 2010 ; Fan et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%